(untitled) (Journal of Advanced Research in Social Sciences, 2024)
The digital era has brought about disruptions that have revolutionized communication. Digitization, the Internet and its inherent innovations have drastically transformed the dissemination of information making it cheaper, faster and easily accessible. However, inadequate content regulation on the Internet has birthed the practice of citizen journalism in the 21st century society, where consumers can easily create and share content online without proper verification. Such content could sometimes be misleading, a trend that has introduced the concept of “fake news” which became more prevalent during the recent Covid-19 pandemic and has continued to pose a problem to journalism practices in the post-Covid era. Similarly, deceptive journalism and the lack of critical assessment of digital media content before creating and disseminating information online poses a challenge to ethical journalistic practices. Thus, it has become pertinent for educational institutions and media professionals in African countries to formally educate students of journalism as well as the wider society on the importance of ethical journalism and the implications of fueling mis-information and mal-information on the Internet. Using the positivist theoretical perspective, the Refracted Publics and Networked Public theories, this study adopts quantitative methods to assess the ethical digital media literacy of Nigerian consumers. It contributes to the wider literature on digital media literacy and ethical journalism education from the context of the Global South, where there is a dearth of such studies. The findings provide insights for improving the journalism pedagogy, whilst ensuring that the core ethical groundings of journalism are not compromised.